The Impacts of Hybrid Fuels on Fuel Efficiency: Reasons and Implications - Zhao Qisen (E3S Web of Conferences)
This paper explores the impact of hybrid fuels on fuel efficiency, environmental sustainability, and economic dynamics. Through a comprehensive review of existing literature and analysis of experimental data, the study examines the potential benefits and challenges associated with the use of blended fuels. Hybrid fuels, comprising mixtures of conventional and alternative energy sources, have shown promise in enhancing fuel efficiency and reducing greenhouse gas emissions. Additionally, they offer potential benefits in stabilizing fuel prices and fostering economic growth by diversifying energy sources. The research also highlights the need for further investigation into optimal fuel mix ratios and their performance across various applications, including automotive, industrial, and power generation sectors. The findings suggest that hybrid fuels could play a crucial role in the transition towards more sustainable and efficient energy systems. This study recommends continued research and development in hybrid fuel technologies to maximize their benefits and address the challenges identified.